1992
DOI: 10.1159/000187028
|View full text |Cite
|
Sign up to set email alerts
|

Intraglomerular Expression of MHC Class II and Ki-67 Antigens and Serum γ-lnterferon Levels in IgA Nephropathy

Abstract: In order to clarify intraglomerular cellular activation and cytokine involvement in IgA nephropathy, the glomerular expression of MHC class II antigens (HLA-DR and DQ) and cellular proliferative nuclear antigen (Ki-67), and serum γ-interferon (γ-IFN) levels were evaluated in 49 patients with IgA nepropathy. HLA-DR was detected in all but 4 patients in whom glomerular sclerosis was present. HLA-DQ and Ki-67 were observed in 51 and 38% of the patients, respectively. Proteinuria, recent macroscopic hematuria, mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 19 publications
2
22
1
Order By: Relevance
“…Anti-TNF-a or soluble re combinant human TNF receptor 1 blocked this ICAM-1 expression [15], In this study, the upregulated glomerular ICAM-1 expression was associated with high levels of cir culating bioactive TNF-a in human glomerulonephritis. The required concentrations of both TNF-a and IFN-y for ICAM-1 expression in cultured endothelial cells were quite similar to the observed serum levels of TNF-a and IFN-y in our present and previous studies [10,11], TNF-a combined with IFN-y could induce ICAM-1 molecules with concentrations of 10-100 times lower than those required for TNF-a or IFN-y alone [32,33]. However, we could not find upregulated interstitial ICAM-1 expression even in cases with high serum TNF-a levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Anti-TNF-a or soluble re combinant human TNF receptor 1 blocked this ICAM-1 expression [15], In this study, the upregulated glomerular ICAM-1 expression was associated with high levels of cir culating bioactive TNF-a in human glomerulonephritis. The required concentrations of both TNF-a and IFN-y for ICAM-1 expression in cultured endothelial cells were quite similar to the observed serum levels of TNF-a and IFN-y in our present and previous studies [10,11], TNF-a combined with IFN-y could induce ICAM-1 molecules with concentrations of 10-100 times lower than those required for TNF-a or IFN-y alone [32,33]. However, we could not find upregulated interstitial ICAM-1 expression even in cases with high serum TNF-a levels.…”
Section: Discussionsupporting
confidence: 90%
“…In human glomerulonephritis, acute nephritis and ac tive lesions of chronic nephritis are associated with infil tration of inflammatory cells such as polymorphonuclear leukocytes, macrophages, and T or B lymphocytes [1], Recently, these phenomena have been shown to be closely related to the expression of cellular adhesion molecules, such as endothelial adhesion molecule 1, intercellular adhesion molecule 1 (ICAM-1), vascular cellular adhesion molecule 1, and major histocompatibility complex class II on glomerular capillary endothelial cells, mesangial cells, or tubular epithelial cells [2][3][4][5][6][7], These dynamic changes of molecular expression may be principally controlled by cytokines such as tumor necrosis factor alpha (TNF-a), interleukin 1 (IL-1 ), and gamma interferon (IFN-y) [8,9], We previously reported the close relationship between serum IFN-y and glomerular expression of major histo compatibility complex class II (HLA-DR and DQ) in human IgA nephropathy and lupus nephritis and that che mokines such as IL-8 and macrophage chemotactic and activating factor correlated with cell infiltration and acti vation in human nephritis [10][11][12][13],…”
Section: Introductionmentioning
confidence: 99%
“…4a) [21,24]. The T cell cytokine IFN--y is well known for its capacity to induce MHC class I, MHC class II and ICAM-l on several cell types [9,10], and it is considered a crucial mediator in the development of a variety of renal diseases [9,25,26]. We could demonstrate the presence of the ICAM-1-inducing cytokines TNF-a and IL-1,3 in rat NCGN at later stages, in agreement with human crescentic glomerulonephritis [4].…”
Section: Immunohistology In Vivomentioning
confidence: 99%
“…Yokoyama et al [20] reported that the serum IFN-y was related to acute exacerbation in patients with IgA GN and played an important role in the immune-mediated glomerular injury of IgA GN. The serum IFN-y that was not detectable in MCNS could be measured with IgA GN and it was related to mesangial cell proliferation in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, cytokines such as tumor necrosis factor (TNF)-a and interferon (IFN)-y have been implicated in glomerular injury [15][16][17][18][19][20], Cytokines have various biolog ical effects including the modulation of cellular prolifera tion, motility, contractility and synthesis of extracellular matrix protein. Some reports demonstrate that expression of these cytokines are increased on the glomeruli in exper imental or human GN [18,[21][22][23][24], However, to our knowledge, there are no reports on the change of these cytokines in the serum at macroH.…”
Section: P<005mentioning
confidence: 99%